On Strongly Positive Multidimensional Arithmetical Sets - Seda N. Manukian (Изд-во НАН РА)
The notion of positive arithmetical formula in the signature (0,=, S), where S(x) = x +1, is defined and investigated in [1] and [2] . A multidimensional arithmetical set is said to be positive if it is determined by a positive formula. Some subclass of the class of positive sets, namely, the class of strongly positive sets, is considered.
Keywords: Mathematics; Algebra